Spiders of the São Paulo state islands, Brazil: redescription of Stenoterommata rassimana (Mello-Leitão, 1923) n. comb. (Araneae, Nemesiidae) - Bertani, Rogério; Mori, André; Fukushima, Caroline Sayuri (Zootaxa, 2017)
Spiders of the islands on the coast of the state of São Paulo, Brazil are poorly known. Herein, we redescribe and discuss the taxonomic position of Psalistops crassimanus Mello-Leitão, 1923, described from Alcatrazes Island and formerly included in the Barychelidae. This species is, herein, transferred to the genus Stenoterommata Holmberg, 1881, Nemesiidae, and the new combination Stenoterommata crassimana (Mello-Leitão, 1923) n. comb. is established. Stenoterommata crassimana males are diagnosed by the very slender and long apical portion of embolus having a strong curvature close to its apex. The females have the spermathecae with single elongate lobe bearing two receptacles. This species is probably endemic to the Alcatrazes Archipelago and Queimada Grande and Queimada Pequena Islands, on the coast of the state of São Paulo, Brazil.